Challenges of Sustainable Tourism Practice in Nigeria - James Chinweuba Egbo; Kingsley Anih; Obianuju Miriam Jonas; Odoh Ejike Peter; Uchechukwu Cyprian Obiokoye (Rekayasa Sipil)
Tourism is recognized as one of the largest industries worldwide in terms of business volume and job creation. Following World War II, tourism was increasingly seen as a strategic tool for development. Sustainable development identifies tourism as a key driver and emphasizes the need for sustainability in tourism planning and development. While the principles of sustainable tourism development are well documented, rural development has yet to fully integrate these principles effectively. This study aims to identify gaps in existing literature and obstacles preventing a comprehensive understanding of sustainable tourism development. A range of both published and unpublished sources, including printed and electronic documents, were critically reviewed to uncover the challenges facing sustainable tourism development.